Analysis Of Factors That Influence Economic Growth And Poverty Levels In Buleleng Regency - Nyoman Aprilianita Harta Dewi; I Ketut Sudibia (International Journal of Management Research and Economics, 2024)
Poverty is a problem often experienced by developing countries. The poverty rate in the North Bali region is still very high when compared with other districts/cities in Bali Province. Therefore, the problem of poverty is a shared responsibility, especially for the government as a supporter of the process of improving people's lives in a government to immediately find a solution in efforts to overcome poverty. The objectives of this study are 1) to analyze the effect of education level, wages and population on economic growth in Buleleng Regency, 2) to analyze the effect of education level, wages, population and economic growth on poverty levels in Buleleng Regency, 3 ) to analyze the level of education, wages, population has an indirect effect on poverty levels through economic growth in Buleleng Regency. The analysis techniques used in this research are descriptive analysis and path analysis. The data used is 13 time series data from 2010-2022. The results of this research show that 1) the level of education has a positive and significant effect on economic growth in Buleleng district, 2) population has a positive and significant effect on the poverty level in Buleleng district 3) Economic growth can mediate the level of education, minimum wage, population on poverty level in Buleleng district. The Buleleng Regency government must continue to carry out programs to improve education and the economy so that poor people can enjoy education and open access to employment opportunities and improve the quality of human resources.